Attorney's Request for Giving an Expert Opinion in the Criminal Procedure Code of the Republic of Kazakhstan: Corrections. Part 2 - I. Sh. Borchashvili; L. F. Paramonova (Теория и практика судебной экспертизы, 2016)
In the second part of the article continued analysis of the stories of the Criminal Procedure Code of the Republic of Kazakhstan, regulating the organization and production of judicial examinations attorney's request. The authors analyzed the rights and duties of experts, made a proposal to adjust the rules based lawyer request for an expert opinion. Considered the rights of the investigating judge in the appointment of judicial examination at the request of the lawyer involved in the criminal trial as an advocate, and taking into account the legal requirements of the relevant rules of the art developed. Proposed alternative language rules governing the rights and duties of the head of the body in the forensic part of the organization and production of judicial examinations attorney's request. In order to standardize a draft procedural document «Advocates' request for an expert opinion».